1268. In Vitro Activity of Ceftazidime-Avibactam and Comparators against KPC-Producing Enterobacterales and Pseudomonas aeruginosa Collected in China as Part of the ATLAS Global Surveillance Program in 2019. (4th December 2021) - Wise, Mark G G; Kazmierczak, Krystyna; Stone, Gregory; Sahm, Daniel F
Abstract: Background: Among Gram-negative bacteria, the rapid spread of carbapenemases has limited therapeutic options. Klebsiella pneumoniae carbapenemase (KPC), an Ambler class A serine β-lactamase, presents a particular challenge as it has become widespread, first identified in an isolate collected in the United States and thereafter moving throughout the world, including China. Fortunately, the β-lactamase inhibitor avibactam is a potent inhibitor of KPC, rendering many Enterobacterales and some P. aeruginosa isolates that carry KPC susceptible to ceftazidime-avibactam (CAZ-AVI) in vitro . This study reports on the in vitro activity of CAZ-AVI and comparators against Enterobacterales and P. aeruginosa isolates collected in China as part of the Antimicrobial Testing Leadership and Surveillance (ATLAS) program in 2019. Methods: 1, 443 non-duplicate Enterobacterales and 522 P. aeruginosa isolates were collected from 17 clinical sites in China in 2019. Susceptibility testing was done using broth microdilution according to CLSI guidelines and interpreted using CLSI 2021 breakpoints. 143/177 meropenem non-susceptible Enterobacterales isolates and 150/187 meropenem non-susceptible P. aeruginosa isolates were interrogated by whole genome sequencing (WGS; Illumina 2x150 bp reads). Results: Enterobacterales isolates exhibited higher % susceptibility (% S) to CAZ-AVI than all comparators tested (96.0% S; Table). The addition of AVI to CAZ resulted in an increase in susceptibility from 61.3% to 96.0% in the overall collection of Enterobacterales isolates. 96.0% of KPC-positive Enterobacterales, and 67.8% of the meropenem non-susceptible sub-population were susceptible to CAZ-AVI, against which comparators were less active (≤42.9 % S). Among P. aeruginosa isolates, 89.8% were susceptible to CAZ-AVI, more than for any comparator except amikacin (AMK; 94.4% S). Against meropenem non-susceptible and KPC-carrying P. aeruginosa sub-populations more were susceptible to CAZ-AVI (75.9% and 83.3% S, respectively) and AMK (87.2% and 100% S, respectively) than to other comparators (≤40.6% and ≤8.3% S, respectively). Results Table Conclusion: CAZ-AVI demonstrated very good in vitro activity against Enterobacterales and P. aeruginosa isolates from China, including those that harbor KPC. Disclosures: Mark G G. Wise, PhD, IHMA (Employee)Pfizer, Inc. (Independent Contractor) Krystyna Kazmierczak, PhD, IHMA (Employee)Pfizer, Inc. (Independent Contractor) Gregory Stone, PhD, AztraZeneca (Shareholder, Former Employee)Pfizer, Inc. (Employee) Daniel F. Sahm, PhD, IHMA (Employee)Pfizer, Inc. (Independent Contractor)